Epigallocatechin-3-gallate antimycotic and azole resistant modulator potential against resistant fungi - Ponte, Tomás Saraiva da (2021)
Project "Resistant mycobiota and mycotoxigenic profile of tea and medicinal plants” (IPL/2020/TEAResMyc_ESTeSL).